Wear of ski waxes: Effect of temperature, molecule chain length and position on the ski base - Rohm, S.; Uterberger, S. H.; Gufler, M.; Putten, M.; Lackner, R.; Nachbauer, W. (Wear, 2017)
Wear of ski wax due to snow friction was determined using FTIR-spectrometry and contact angle measurements. Wear of snow was measured using computer tomography. • Snow temperature effected wear with high wax wear on cold and low wax wear on warm snow. • Wear of ski wax was higher in the ski tip region than in the ski tail region. • Higher wax chain length led to less wax wear on cold snow and to less friction on snow close to the melting point.